2020
DOI: 10.1587/transinf.2018edp7409
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Axis-Wise Triaxial Acceleration Data Fusion in CNN-Based Human Activity Recognition

Abstract: The triaxial accelerometer is one of the most important sensors for human activity recognition (HAR). It has been observed that the relations between the axes of a triaxial accelerometer plays a significant role in improving the accuracy of activity recognition. However, the existing research rarely focuses on these relations, but rather on the fusion of multiple sensors. In this paper, we propose a data fusion-based convolutional neural network (CNN) approach to effectively use the relations between the axes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For example some researchers used deep learning to improve the performance of HAR systems [12][13][14]. While others focused on enhancing quality of DL by increasing the information in the training phase [15,16] or by adapting the sensor data [17,18]. Also M. Zeng et al [19] preferred to use DL technique after comparing it with traditional machine learning and finding that DL achieved higher accuracy.…”
Section: Motivations and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example some researchers used deep learning to improve the performance of HAR systems [12][13][14]. While others focused on enhancing quality of DL by increasing the information in the training phase [15,16] or by adapting the sensor data [17,18]. Also M. Zeng et al [19] preferred to use DL technique after comparing it with traditional machine learning and finding that DL achieved higher accuracy.…”
Section: Motivations and Literature Reviewmentioning
confidence: 99%
“…However, there are trends in many studies to suggest that there are two problems in activities confusions [12,[16][17][18][19][56][57]: Group1 (walking, up and downstairs) and Group2 (sit, stand). For more explanation, experiments results of J. Lee et al [57] showed that 6% of ascending activity was incorrectly classified as walking but 5% of walking activity was incorrectly classified as ascending stairs.…”
Section: User-independentmentioning
confidence: 99%
See 1 more Smart Citation